STUDI DIAGNOSTIK BEBERAPA KOLEKSI MUSEUM KAYU WANAGAMA I - , ELIZABETH SUSTIN S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Wood is the best material for use in the manufacture of cultural objects, either in the form of functional objects and objects of art to appreciate the taste. Cultural objects, including stored as a collection in a museum, containing the value of the noble / high-aspaek aspects: cultural, social, archeology, history, science, and technology and economics. Value and function of the museum's collection was inspired appearance of such a thought in national and international order, that the existence of the museum collection shall be maintained. Effort to maintain the existence of a collection of attention and encouragement that the greater, because the wood is very susceptible to damage caused by biotic and non-biotic factors. The experiment was conducted at the wood Museum Wanagama I which is located in the village Bunder, district Playen, Gunung Kidul district and Laboratory Section of Forest Products Technology, Faculty of Forestry UGM. Implementation of the initial data collection carried out in September 2013. Research was an activity to maintain the existence of a collection called collection conservation/cultural heritage made of wood, which covers the conservation of heritage objects are made from wood (BCBBK). Based on the exposure study, the conclusions that can be drawn in this study the type of wood making up the museum's collection of wood Museum Wanagama I that includes Rice ladle (1 unit) derived from wood Sengon Sea (Paraserianthes falcataria), Tray (1 unit) derived from wood Sengon Sea (Paraserianthes falcataria), mask (5 units) all come from Teak wood (Tectona grandis) and Box Jewelry (1 unit) derived from Teak wood (Tectona grandis). Latest condition of objects of collections of wood Museum Wanagama I observed, covering Centong 1 unit, tray 1 unit, 1 unit Jewellery Box and mask 5 units. In wooden mask 3 has been found physical damage such as broken and the wooden mask 5 due to fungi.